Note: Energy convexity and density matrices in molecular systems - Bochicchio, R.C. (2012)
A novel appropriate definition for the density matrix for an interacting Coulombic driven atomic or molecular system with non-integer number of particles is given. Our approach leads to a direct derivation of the proposal reported by Perdew [Phys. Rev. Lett. 49, 1691 (1982)]10.1103/PhysRevLett.49.1691 and points out its suitability and perspective advances. © 2012 American Institute of Physics.